2021
DOI: 10.1177/1524838021998305
|View full text |Cite
|
Sign up to set email alerts
|

Help-Seeking and Barriers to Care in Intimate Partner Sexual Violence: A Systematic Review

Abstract: Intimate partner sexual violence (IPSV) is a prevalent phenomenon, yet an under-researched topic. Due to the complex nature of balancing love and fear, individuals who experience IPSV have unique needs and face unique barriers to seeking care. The purpose of this systematic review was to examine the literature on help-seeking and barriers to care in IPSV. Articles were identified through PubMed, CINAHL, PsycINFO, and Web of Science. Search terms included terms related to IPSV, intimate partner violence (IPV), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 77 publications
5
39
0
1
Order By: Relevance
“…In developed countries like Australia and the UK, maternal mental health screening is integral to routine care, while in Vietnam and other Asian countries, it is rarely considered unless a woman's condition is very severe and obvious (Koirala & Chuemchit, 2020). This study confirmed findings from previous studies that a lack of clinical training is a major barrier for IPV screening and improvement in psychosocial antenatal care practice (Githui et al, 2018;Hasselle et al, 2020;Wright et al, 2021).…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…In developed countries like Australia and the UK, maternal mental health screening is integral to routine care, while in Vietnam and other Asian countries, it is rarely considered unless a woman's condition is very severe and obvious (Koirala & Chuemchit, 2020). This study confirmed findings from previous studies that a lack of clinical training is a major barrier for IPV screening and improvement in psychosocial antenatal care practice (Githui et al, 2018;Hasselle et al, 2020;Wright et al, 2021).…”
Section: Methodssupporting
confidence: 85%
“…A reasonable approach to tackle this difference could be to make the services available for victims, such as shelters or free hotlines, more easily accessible. Specialist training should also be made available to professionals working with victims and their families so that they are better equipped to provide high-quality care (Hasselle et al, 2020;Wright et al, 2021). These suggestions correspond with Le et al (2019) who found that to improve monitoring and evaluation mechanisms, the quality of training for health workers should focus on effectively implementing policies for domestic violence prevention in local settings.…”
Section: Evidence-informed Actions In Hue Citymentioning
confidence: 94%
See 2 more Smart Citations
“…(19. ) Apua väkivaltaan liittyviin ongelmiin ja oirei siin haetaan pääasiassa sosiaali ja tervey den huol losta (20)(21). Nämä tahot ovat siten avain ase massa väkivallan tunnistamisessa ja siihen puut tumisessa.…”
unclassified